2008
DOI: 10.1128/jvi.00646-08
|View full text |Cite
|
Sign up to set email alerts
|

Human Endogenous Retrovirus K (HML-2) Elements in the Plasma of People with Lymphoma and Breast Cancer

Abstract: Actively replicating endogenous retroviruses entered the human genome millions of years ago and became a stable part of the inherited genetic material. They subsequently acquired multiple mutations, leading to the assumption that these viruses no longer replicate. However, certain human tumor cell lines have been shown to release endogenous retroviral particles. Here we show that RNA from human endogenous retrovirus K (HERV-K) (HML-2), a relatively recent entrant into the human genome, can be found in very hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
205
0
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(221 citation statements)
references
References 58 publications
5
205
0
3
Order By: Relevance
“…For insertion polymorphisms, although most HERV families became integrated into the human genome millions of years ago, a new class of insertionally polymorphic HERV-K family members has recently been described (46,47). HERV-K113 and HER-K115 insertion has been reported to be involved in various types of cancer (48)(49)(50)(51). New insertion polymorphism of HERVs could serve as novel genetic risk factors and thus provide new insight for research into HERV LTR and cancer.…”
Section: Effect Of Possible Mechanisms Of Herv Ltr In Cancermentioning
confidence: 99%
“…For insertion polymorphisms, although most HERV families became integrated into the human genome millions of years ago, a new class of insertionally polymorphic HERV-K family members has recently been described (46,47). HERV-K113 and HER-K115 insertion has been reported to be involved in various types of cancer (48)(49)(50)(51). New insertion polymorphism of HERVs could serve as novel genetic risk factors and thus provide new insight for research into HERV LTR and cancer.…”
Section: Effect Of Possible Mechanisms Of Herv Ltr In Cancermentioning
confidence: 99%
“…HERV type K of the HML2 subtype is the most recently integrated and most intact retrovirus in the human genome (19). These most recently acquired proviruses of the HERV-K family can express viral proteins and produce viral particles (20,21). In previous studies we reported that expression of HERV-K env protein in malignant BC cells was substantially higher than in normal or nonmalignant breast cells (22)(23)(24), suggesting that HERV-K might be reactivated and implicated in carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, external stimuli, such as infections, viral transactivators, chemical exposures, cytokines, hormones, and inflammation, can induce expression of these proviruses (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). We and others have shown that HIV-1 infection is associated with increased HERV-K (HML-2) expression in vitro and in vivo (33,(45)(46)(47)(48)(49)(50)(51)(52)(53). Compared to healthy individuals, HIV-1-infected individuals show high levels of HERV-K (HML-2) RNA, DNA, protein, and viral particles in their plasma (45,47,48,50).…”
mentioning
confidence: 99%